Exercise Capacity in Prepubertal Children with Cystic Fibrosis. (10th May 2012) - Kilbride, Emma; Widger, John; Hussey, Juliette; El Nazir, Basil; Greally, Peter
Abstract : Background . Patients with cystic fibrosis (CF) are observed to have diminished lung function, nutritional status, and aerobic exercise capacity. All three parameters are related to prognosis and survival. However, there is little information regarding these parameters in prepubertal patients. Methods . Our study groups consisted of sixteen patients with CF (7 girls) and 99 healthy volunteers (52 girls). Subjects performed spirometry and a progressive exercise test to exhaustion on a cycle ergometer. Leg muscle strength was measured using an isokinetic dynamometer. Physical activity was examined using the modifiable activity questionnaire and accelerometer. Results . Nutritional status was similar between groups (BMI—boys control versus CF 18.5 versus 17.9, girls control versus CF 19.5 versus 17.4). Girls with CF were significantly smaller and lighter than controls. Lung function was significantly reduced in CF groups (FEV1 —boys control versus CF 91% versus 84%, girls control versus CF 90% versus 82%). Patients with CF were as active and as fit as their healthy controls. Conclusion . In this group of prepubertal children with CF, nutritional status was comparable to healthy children of the same age. Their aerobic exercise tolerance and peripheral muscle strength were also relatively well preserved despite significantly lower lung function.